2012
DOI: 10.1242/jcs.088286
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian erythroblast enucleation requires PI3K-dependent cell polarization

Abstract: SummaryEnucleation, the final step in terminal differentiation of mammalian red blood cells, is an essential process in which the nucleus surrounded by the plasma membrane is budded off from the erythroblast to form a reticulocyte. Most molecular events in enucleation remain unclear. Here we show that enucleation requires establishment of cell polarization that is regulated by the microtubule-dependent local activation of phosphoinositide 3-kinase (PI3K). When the nucleus becomes displaced to one side of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 42 publications
(62 reference statements)
3
62
1
Order By: Relevance
“…By overlapping the regions of alternatively skipped exons and their flanking introns with published MBNL1 CLIP-seq binding clusters, 31 we observed a significant enrichment of MBNL1 binding clusters in erythropoiesis-associated SE events (P 5 1.8 3 10…”
Section: Evidence For Involvement Of Mbnl1 In Global Splicing Changesmentioning
confidence: 88%
See 1 more Smart Citation
“…By overlapping the regions of alternatively skipped exons and their flanking introns with published MBNL1 CLIP-seq binding clusters, 31 we observed a significant enrichment of MBNL1 binding clusters in erythropoiesis-associated SE events (P 5 1.8 3 10…”
Section: Evidence For Involvement Of Mbnl1 In Global Splicing Changesmentioning
confidence: 88%
“…30 Therefore, our observation of MBNL motif enrichment downstream of the regulated exons suggested that MBNL proteins binding to these sites regulate inclusion of the cassette exon. By overlapping the regions of alternatively skipped exons and their flanking introns with published MBNL1 CLIP-seq binding clusters, 31 we observed a significant enrichment of MBNL1 binding clusters in erythropoiesis-associated SE events (P 5 1.8 3 10…”
Section: Evidence For Involvement Of Mbnl1 In Global Splicing Changesmentioning
confidence: 88%
“…These include genes involved in EpoR signaling, enucleation, 61,62 and stress erythropoiesis 63 (Table 2). PLEK2 (Pleckstrin-2) and DYRK3 both have proven roles in terminal erythroid differentiation, 63,64 and both are expressed at ,10% of wildtype levels in the proband.…”
Section: Klf1 Regulates Key Cell-signaling Moleculesmentioning
confidence: 99%
“…3 The most striking visual aspect of this erythropoietic maturation is the last step, when the orthochromatic erythroblast goes through remarkable undulations, like a pot coming to boil, with the bulk of its cytoplasm pulling away from the nucleus until it divides into 2 very different cells. 1,4 The enucleated reticulocyte continues to mature into the functional RBC. The other cell, a pyrenocyte containing the condensed nucleus surrounded by a thin layer of cytoplasm, signals the macrophage that it is the half to be eaten by exposing phosphatidylserine on its cellular membrane.…”
mentioning
confidence: 99%
“…Because KIR receptors are inhibited by autologous HLA class C molecules, many clinical investigators have chosen to infuse allogeneic NK cells to ensure that they can kill recipient tumor cells. [2][3][4] Several clinical trials have revealed the potential of NK cells as an immunotherapy, but barriers to their wider efficacy have included both their tolerance to self-major histocompatibility complex molecules and their susceptibility to immunosuppressive elements that are present at the sites of many tumors. These elements include inhibitory cytokines, myeloid-derived suppresser cells, and Tregulatory cells (Tregs).…”
mentioning
confidence: 99%